Audience and reception in the early modern period
1 online resource.
Keywords: "Early modern audiences, readerships, and viewerships were not homogenous. Differences in status, education, language, wealth, and experience (to name only a few variables) could influence how a group of people, or a particular person, received and made sense of sermons, public proclamations, dramatic and musical performances, images, objects, and spaces. The ways in which each of these were framed and executed could have a serious impact on their relevance and effectiveness. The chapters in this volume explore the ways in which authors, poets, artists, preachers, theologians, playwrights, and performers took account of and encoded pluriform potential audiences, readers, and viewers in their works, and how these varied parties encountered and responded to these works. The contributors here investigate these complex interactions through a variety of critical and methodological lenses"--